2021
DOI: 10.1097/wnr.0000000000001569
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of silent information regulator 1 alleviates mitochondrial dysfunction in the trigeminal nucleus caudalis in a rat model of chronic migraine

Abstract: Although the mechanism of chronic migraine is still unclear, more and more studies have shown that mitochondrial dysfunction plays a possible role in migraine pathophysiology. Silent information regulator 1 (SIRT1) plays a vital role in mitochondrial dysfunction in many diseases. However, there is no research on the role of SIRT1 in mitochondrial dysfunction of chronic migraine. The aim of this study was to explore the role of SIRT1 in mitochondrial dysfunction in chronic migraine. A rat model was established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…It plays a central role in controlling mitochondrial function and mitochondrial biogenesis and is a known positive regulator of mitochondrial function and oxidative metabolism ( Fernandez-Marcos and Auwerx, 2011 ; Wang et al, 2015 ). It was found that repeated infusion of inflammatory soup into the dura mater could decrease the expression of PGC-1α in the trigeminal nucleus caudalis (TNC) in SD rats ( Figure 4 ) ( Liang et al, 2021 ).…”
Section: Relationship Between Reactive Oxygen Species and Migrainementioning
confidence: 99%
“…It plays a central role in controlling mitochondrial function and mitochondrial biogenesis and is a known positive regulator of mitochondrial function and oxidative metabolism ( Fernandez-Marcos and Auwerx, 2011 ; Wang et al, 2015 ). It was found that repeated infusion of inflammatory soup into the dura mater could decrease the expression of PGC-1α in the trigeminal nucleus caudalis (TNC) in SD rats ( Figure 4 ) ( Liang et al, 2021 ).…”
Section: Relationship Between Reactive Oxygen Species and Migrainementioning
confidence: 99%
“…As mentioned previously, releases of neuropeptides such as CGRP, substance P and PACAP-38 are notable components of NI and these peptides are also linked to migraine pathophysiology, especially CGRP. Chronic application of IS on the dura causes upregulation of CGRP genes [ 62 , 63 , 66 , 67 , 73 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ] and Substance P [ 76 , 80 , 81 , 82 ] in the TGVS. PACAP-38 is increased in the plasma of migraineurs during attacks but reduced in chronic migraineurs [ 84 , 85 ].…”
Section: The Inflammatory Soup (Is) Model and Its Variantsmentioning
confidence: 99%
“…Other notable pathological alterations caused by IS application to the dura include a decrease of 5-HT in the brain [ 65 ], an increase in the 5-HT 7 receptor expression [ 64 ], a decrease in α7nACh receptor expression in the hippocampus [ 75 ], an increase in nitric oxide (NO) [ 79 ], increases in the warm receptor TRPV1 [ 65 ] and cold receptor TRPM8 [ 87 ] expression, decreases in SIRT1 and PGC-1α [ 80 ], mitochondrial dysfunction [ 80 , 88 ], an altered functional connectivity between various brain regions [ 68 , 89 , 90 , 91 , 92 ], an increase in EphB2/EphrinB2 receptors [ 81 ], increased synaptic plasticity in TNC [ 76 , 79 , 81 ] but decreased plasticity in the hippocampus [ 93 ], an increase in glutamate in the TNC [ 94 ], an increase in mGluR5 [ 95 ], a decrease in GABA [ 94 ], decreases in GABABR1 and GABABR2 [ 94 ], increases in mTOR and autophagy [ 95 ], an increase in ASIC3 receptor expression [ 66 , 82 ], the increase of nNOS in the brain of rhesus monkeys [ 83 ], the impairment of descending inhibitory pathways [ 96 ], an increase in nerve growth factor (NGF) [ 66 ], increases of the P2Y 14 receptor [ 59 ] and the P2X 4 receptor expression [ 67 ], an increase in BBB permeability [ 74 , 97 ], the increase of VEGF [ 97 ], the sensitization of trigeminovascular neurons [ 96 , 98 , 99 , 100 , 101 ], an increase in white matter in different brain regions [ 102 ] and changes in the gut microbiota [ 65 ]. The application of other c...…”
Section: The Inflammatory Soup (Is) Model and Its Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, several nutrients targeting energy production and mitochondrial metabolism have shown efficacy in preventing migraine, such as riboflavin, coenzyme Q 10 , thiamine and niacin [ 7 9 ]. In migraine rodent models, mitochondrial dysfunction was also observed [ 10 ]. Thus, improving mitochondrial function has promise as an effective treatment for migraine.…”
Section: Introductionmentioning
confidence: 99%